Anti-nmda receptor encephalitis complicating hsv encephalitis with demonstrated seroconversion. Issue 5 (8th May 2017) - Swayne, Andrew; Brown, Helen; Singh, Gaurav; Blum, Stefan
Abstract : Objectives: A case of anti-NMDA receptor antibody encephalitis seen at a tertiary neurology centre complicating initial herpes simplex virus encephalitis (HSVE) is presented. HSVE is the most frequent fatal encephalitis in western countries with 35% of patients affected by this condition suffering adverse outcomes. 1 Relapsing post-HSVE is a potentially lethal complication that occurs in 13%–24% of patients. 2 Relapses may either be infectious or immune based in origin with cases such as the one presented illustrating greater understanding of immune based processes such as NMDA-R encephalitis allowing earlier detection and therapeutic intervention. Case: A 65 year old female was found collapsed with a decreased level of consciousness. Examination revealed her to be in septic shock with decreased level of consciousness, necessitating intubation. CSF was positive for HSV1 DNA. After treatment and clinical improvement with acyclovir for the initial diagnosis of HSV1 encephalitis, the patient deteriorated requiring reintubation. A repeat CSF sample was negative for HSV1 DNA, but positive for anti-NMDA receptor antibodies in both serum and CSF. The patient improved with immune based therapy. On retrospective analysis anti-NMDA receptor antibodies had been negative in initial CSF and blood samples. Conclusions: The discovery and clinical application of anti-NMDA receptor antibodies has helped to define the mechanism behind immune based relapse of HSVE. This case illustrates the utility of testing for anti-NMDA receptor antibodies during the early work-up for HSVE as demonstrating seroconversion can help to guide switching from anti-viral to immune therapy.